2021
DOI: 10.3390/ani11072002
|View full text |Cite
|
Sign up to set email alerts
|

Tail-Biting in Pigs: A Scoping Review

Abstract: Tail-biting is globally recognized as a welfare concern for commercial swine production. Substantial research has been undertaken to identify risk factors and intervention methods to decrease and understand this vice. Tail-biting appears to be multifactorial and has proven difficult to predict and control. The primary objective of the scoping review was to identify and chart all available literature on the risk factors and interventions associated with tail-biting in pigs. A secondary objective was to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 118 publications
1
13
0
Order By: Relevance
“…In all cases, tail biting is connected with poor welfare of pigs because of the pain and stress (Munsterhjelm et al, 2013). Tail biting is multifactorial (Taylor et al, 2010) and has been proven difficult to predict and control (Henry et al, 2021). The risk of tail biting is increased in the conditions of poor management and housing practices that do not meet the basic requirements of pigs, thereby causing stress.…”
Section: 7mentioning
confidence: 99%
“…In all cases, tail biting is connected with poor welfare of pigs because of the pain and stress (Munsterhjelm et al, 2013). Tail biting is multifactorial (Taylor et al, 2010) and has been proven difficult to predict and control (Henry et al, 2021). The risk of tail biting is increased in the conditions of poor management and housing practices that do not meet the basic requirements of pigs, thereby causing stress.…”
Section: 7mentioning
confidence: 99%
“…Despite decades of research, tail biting is still a major problem in intensive pig production. Tail biting has serious consequences for the animals involved because it leads to physical injury and pain as well as psychological stress 1 , 2 . Tail biting also has a negative impact on the economic performance of pig farms 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis and etiology of these five common pathological conditions, which cause important loses in porcine production, are diverse and multifactorial. It has been reported that tail-biting lesions are highly related to stressful housing conditions that produce excessive motivation for biting ( 43 ). However, tail-biting lesions are also suggested to be an indication of serious stress experienced by the victims ( 44 ).…”
Section: Discussionmentioning
confidence: 99%